Analysis of the relationship between leadership style and teacher work motivation in vocational high schools - Ermita Ermita; Nelitawati Nelitawati; Indra Jaya; Nur Alifah Ulfi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Leaders who effectively apply a leadership style can realize their goals by providing motivation. The purpose of this research is to find out and obtain information about the leadership style of school principals and teacher work motivation at SMKN 6 Padang. This research is quantitative research with a correlational approach. The research population is 100 teachers at SMKN 6 Padang, while the sample in this study was 50 teachers taken using Proportional Stratified Random Sampling calculated using the Slovin formula. The instrument used was a Likert Scale model questionnaire with five alternative answers whose results were valid and reliable. Analysis in this research uses the SPSS 24.0 program to process and analyze normality, linearity and significance tests of the relationship between the two variables. The results of this research indicate that there is a positive and significant relationship between leadership style and teacher work motivation, which means that the principal's leadership style has a positive and significant relationship with teacher work motivation. The implication of the results of this research is to increase work motivation through the principal's leadership style, namely increasing the task-oriented leadership style of the principal. In addition, the results of this study show that the interpretation of the principal's leadership style towards subordinates is greater than the interpretation of the principal's task-oriented leadership style.